Implementation of Yorùbá Language Multimedia Learning System - Eludiora, Safiriyu Ijiyemi; Akinbande, Olamide A. (Transactions on Engineering and Computing Sciences, 2017)
The use of multimedia learning system has been widely accepted as a useful and effective tool in the field of human language. Many students and researchers have examined multimedia learning’s effectiveness from a number of aspects, including four skills of learning: listening, speaking, reading (including vocabulary comprehensive) and writing. However, the effectiveness of multimedia in human language hasn’t been well explained. The goal of this study was to develop a multimedia learning system for a fresh learner of Yorùbá language by introducing the Yorùbá alphabets and their respective words. In particular, this study investigates the relative efficiency of three different modes used in teaching Yorùbá language alphabets, directional complements: text only, text with a still picture and text with audio clips. In other to develop the system, many traditional textbooks, and written theses on Yorùbá alphabets are consulted for effective study of the alphabets and their possible words. Java programming language was used for the implementation of the multimedia platform. After the implementation of this study, the platform will enable users to interact with a desktop and web-based Yorùbá alphabets multimedia environment where easy and effective identification of Yorùbá language alphabets. The platform will teaches on how to pronounce words from Yorùbá language alphabets. In conclusion, Yorùbá alphabet multimedia learning system provides efficient means of writing, reading and speaking Yorùbá language.